AB1171 Ultrasound assessment of the knee in elderly japanese population. (12th June 2018) - Okahata, A.; Ito, H.; Furu, M.; Kuriyama, S.; Nakamura, S.; Ishikawa, M.; Morita, Y.; Azukizawa, M.; Hamamoto, Y.; Tanaka, Y.; Tabara, Y.; Matsuda, F.; et al.
Abstract : Background: Osteoarthritis (OA) is known as degenerative arthritis. Knee OA is a common disease among aged population and one of the leading causes of disability. Many modalities are used to evaluate bony abnormalities and joint space narrowing for knee OA. Ultrasound is one of the imaging modalities for evaluating knee joint structures such as cartilage, meniscus, osteophyte and synovium. There are few large-scale studies focused on ultrasound findings of the knee of the elderly in general population. Objectives: The aim of our study is to evaluate relationship between clinical and ultrasound findings of the elder population. Methods: Two hundred and twenty two participants were recruited from Nagahama residents aged 60 years or older. We evaluated the both knees of participants with ultrasound with a 5MHz transducer. Ultrasound scans were performed and assessed by a standardised protocol of the Outcome Measures in Rheumatoid Arthritis Clinical Trial Guidelines. The symptoms were clinically assessed by using Knee Society Score 2011 (KSS). We statistically examined whether the KSS(symptom) correlated with other clinical parameters and each ultrasonographical findings. Results: Participants were 65 men and 137 women with a mean age of 67±5 years old. The mean body mass index (BMI) was 21.8±2.76 kg/m 2 . The symptom subscale of KSS were significantly associated with age, BMI, knee maximum extension and flexion angle, suprapatellar effusion, medial meniscus protorusion, medial recess synovial hypertorophy, and femoral and tibial medial osteophytes. Multiple regression analysis showed that medial osteophytes was most closely related to the symptom subscale of KSS among the ultrasound findings and demographic data evaluated. Conclusions: The present study showed a strong association between the symptoms of the knee and the medial osteophytes in Japanese elder population. References: [1] Linaker CH, et al. Clin Rheumatol1999. [2] S. Saarakkala, et al.Osteoarthritis and Cartilage2012. [3] Schmidt WA, et al. Ann Rheum Dis2004. [4] Wakefield RJ, et al. J Rheumatol2005 Disclosure of Interest: None declared